Building a Performance Management System for Hospitals Based on Diagnosis-Related Group (DRG) Payment. (19th March 2022) - Zhao, Shaolin; Gu, Yingying; Huang, Zhenju
Abstract : With the deepening of the national medical and health system reform, various supporting reform measures are being promoted. The reform of medical insurance payment methods is an important part of the process, and payment through diagnosis-related groups (DRGs) will gradually become the main way for medical insurance to pay medical institutions. According to the analysis of the impact of DRG payment on hospital performance management, this research examines the construction and implementation of the internal performance management system (IPMS) based on DRG payment in hospitals. The IPMS based on DRG payment includes four elements: organizational management system, assessment system, communication and feedback system, and information support system. In addition, this study explores how IPMS can be implemented in hospitals, including the preparation before implementation, key points to be grasped during implementation, and considerations to be focused on.